Vascular and renal hemodynamic changes after renal denervation - Ott, Christian; Janka, Rolf Matthias; Schmid, Axel; Titze, Stephanie; Ditting, Tilmann; Sobotka, Paul A.; Veelken, Roland; Uder, Michael; Schmieder, Roland (Clinical Journal of the American Society of Nephrology, 2013)
Background and objectives Renal denervation (RDN) has been shown to be effective in reducing BP in treatmentresistant hypertension. Measurement of the renal and sympathetic activity revealed a decrease in sympathetic drive to the kidney and small resistance vessels after RDN. However, the consequences on renal perfusion and renal vascular resistance (RVR), as well as central hemodynamics, are unknown. Design, setting, participants, & measurements Nineteen patients with treatment-resistant hypertension (office BP140/90mmHg, despite at least three antihypertensive drugs [including a diuretic], and diagnosis confirmed by 24-hour ambulatory BPmonitoring) underwent RDNbetween January andOctober 2011. Renal perfusion and RVR were noninvasively assessed by magnetic resonance imaging with arterial spin labeling, and renal function was assessed by estimating GFR before (day 21), after (day +1), and again after 3 months of RDN. Central hemodynamics was assessed using pulse wave analysis at day 21 and after 6 months of RDN. Results Peripheral office BP (systolic, 158±26 versus 142±23mmHg, P=0.002; diastolic, 83±13 versus 76±9mmHg, P=0.02) and mean systolic 24-hour ambulatory BP (159±17 versus 152±17 mmHg, P=0.02) were significantly reduced 6 months after RDN. Renal perfusion was not statistically different between day 21 and day +1 (256.8 [interquartile range (IQR), 241-278] versus 263.4 [IQR, 252-277] ml/min per 100 g; P=0.17) as well as after 3 months (256.8 [IQR, 241-278] versus 261.2 [IQR, 240-285] ml/min per 100 g; P=0.27) after RDN. RVR dropped (432.1 [IQR, 359-525] versus 390.6 [IQR, 338-461] AU; P=0.02), whereas renal function was not statistically different at any time point. Central systolic BP (145±31 versus 131628 mmHg; P=0.009), diastolic BP (85±18 versus 80±14 mmHg; P=0.03), and central pulse pressure (61±18 versus 52±18 mmHg; P=0.02) were significantly reduced 6 months after RDN. Central augmentation index (24±8 versus 20±8%; P=0.02) was decreased 6 months after RDN. Conclusion The data indicate that RDN significantly reduced peripheral and central BP. Despite reduced systemic BP, renal perfusion and function did not change after RDN. © 2013 by the American Society of Nephrology.
CRIS-Team Scopus Importer:2023-03-08